HUKUM KEPEMILIKAN BARANG TAMBANG PERSPEKTIF FIQH MUAMALAH - Wedi, Wedi Pratanto Rahayu; Syai'in, Syai'in (SHAKHSIYAH BURHANIYAH: Jurnal Penelitian Hukum Islam, 2024)
Ownership of mining goods provides enormous benefits for the owner. It is very important that there is appropriate law to regulate it. This research aims to find the law of ownership of mining goods, a muamalah fiqh perspective. The results of the research are according to fiqh muamalah that mining goods can be owned by ihraz al-Mubahat and the majority of ulama said that mining goods can be owned by individuals, while Malikiyah ulama said that mining goods can only be owned by the state, and the ownership of mining goods must be based on aqidah , morals, justice and maslahat.